QUALITY ASSURANCE IN SPECIALIZED TRANSLATION (SYNERGETIC ASPECTS) - Dorofeyeva, Margarita (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The paper presents a synergetic information technique of comparative translation analysis in specialized translation based on the synergetic information model. The synergetic comparative translation analysis was demonstrated on material of the German text fragment by Sigmund Freud, its control translation into Ukrainian and also on standard Ukrainian translation, published in a book. The research object builds the synergetic information technique of comparative translation analysis in specialized translation from German into Ukrainian. The subject of the study includes implementation peculiarities of the methodology by carrying out the synergetic comparative translation analysis. During the synergetic analysis the instable equilibrium relations between the source text and target text as well as translation mistakes in the intercultural specialized communication were investigated. The synergetic translation analysis allows to identify types and language levels of the translator’s information deficit, and beyond that information types related to translation mistakes on the corresponding levels in the self-organized translation system. The procedural stages of the analysis make it possible to determine the translation dominant of the source text, the causes for translation information deficits and their compensation strategies. The reconstruction of incorrect translation solutions in the target text makes a contribution to better understanding self-organized translation processes that correspond to the development phase of the synergetic translation system. The synergetic information technique of translation analysis helps to discover the synergetic mechanisms in translation, thus realizing quality assurance as editing, correction and objective evaluation of the source text. Beyond that the synergetic translation analysis algorithm proved successful in the minimizing the future translator’s mistakes in specialized texts translation. ______________ References • German I. Lingvosinergetika: Monografiya [Linguosynergetics: Monograph]. Barnaul, Altajskaja akademia ekonomiki i prava Publ., 2000, 168 p. (In Rus.) • Dorofeyeva M. Synerhetychno-informatsiyna metodyka perekladats’koho analizu [Synergetic Information Method of Translation Analysis]. Naukovyy visnyk Khersons’koho derzhavnoho universytetu. Seriya: Perekladoznavstvo ta mizhkul’turna komunikatsiya. 5. Kherson, 2016, pp. 12-17. (In Ukr.) • Dorofeyeva M. S. .Synerhetyka perekladu spetsial’nykh tekstiv (nimets’ko-ukrayins’kyy napryam): Monohrafiya [Synergetics of Specialized Texts Translation (German-Ukrainian Direction): Monograph]. Kyiv, Vydavnychyy dim Dmytra Buraho Publ., 2017, 520 p. (In Ukr.) • Knyazeva Ye., Kurdyumov S. Osnovaniya sinergetiki: Chelovek, konstruiruyushhij sebya i svoe budushhee [Foundations of Synergetics. A Person who Constructs himself and his Future]. Moscow, Knizhnyj dom «LIBROKOM» Publ., 2011, 264 p. (In Rus.). • Min’jar-Beloruchev (1996). Teorija i metody perevoda [Translation Theory and Methods]. Moscow, Mosk. Licej Publ., 1996, 208 p. (In Rus.). • Müller V. Das große deutsch-ukrainische Wörterbuch. Etwa 170 000 Wörter und Wortverbindungen. Кyiv, Chumats’kyy Schlyakh, 2005, 792 p. • Sinergetika v filologicheskih issledovaniyah: monografiya [Synergetics in Philological Studies. Monograph]. Kharkiv: KhNU imeni V.N.Karazina, 2015, 340 p. (In Rus.). • Stepanov Yu. Yazyk i metod. K sovremennoj filosofii yazyka [Language and Method. To the Modern Philosophy of Language]. Moscow, Yazyki russkoj kul’tury Publ., 1998, 784 p. (In Rus.). • Stepin V. Filosofija nauki. Obshhie problemy [Philosophy of Science. Common Problems]. Мoscow, Gardariki Publ., 2006, 384 p. (In Rus.). • Freud S Vstup do psykhoanalizu / z nim. P.Tarashchuka. [Introduction to Psychoanalysis/ Translated from German by P. Taraschuk] Kyiv, Оsnovy Publ., 1998, 709 p. (In Ukr.) • Haken H. Sinergetika [Synergetics]. Moscow, Mir Publ., 1980, 404 p. (In Rus.). • Haken H. Ierarhii neustojchivostej v samoorganizujushhihsja sistemah i ustrojstvah [Hierarchy of Fluctuations in Self-organizing Systems and Devices] Moscow, Mir Publ., 1985, 424 p. (In Rus.). • Khybni protsesy [Wrong Actions]. Control version of the translation into Ukrainian 1.1, Handout. • Freud S. Vorlesungen zur Einführung in die Psychoanalyse. Erster Teil. Frankfurt am Main, Fischer Verlag, 2007, 409 S. • Haken Hermann et al. Beiträge zur Geschichte der Synergetik. Allgemeine Prinzipien der Selbstorganisation in Natur und Gesellschaft. Wiesbaden, Springer Verl., 2016, 319 S. • Hoffmann Chr., Krott A. Einführung in die Synergetische Linguistik. Korpuslinguistische Untersuchungen zur quantitativen und systemtheoretischen Linguistik, 2002, pp. 1-29. • Köhler R. Elemente der synergetischen Linguistik. Glottometrika 12, 1990, S. 179-187. • Nord Ch. Text Analysis in Translation, Amsterdam, Rodopi B.V., 1991, 164 p. • Reiss K. Grundfragen der Übersetzungswissenschaft: Wiener Vorlesungen. Wien: WUV-Univ.-Verlag, 2000, 132 S. • Duden Online-Wörterbuch. Available at: http://duden.de (accessed 1.03.2018).